Epidermal cyst of submandibular gland - Prepageran, Narayanan; Rahmat, O.; Kuljit, S. (Malaysian Medical Association, 2005)
The differential diagnosis of a cystic lesion in the submandibular area can be difficult. We report a case of epidermal cyst of submandibular gland which is relatively rare compared to the commoner epidermoid cyst.